The importance of early detection for postoperative maxillary cyst before dental implantation: A case report. (September 2021) - Funakawa, Tatsuo; Kawanabe, Hitoshi; Usami, Akinobu; Takahashi, Keiso; Kato, Yasumasa; Baba, Yuh
Abstract: Introduction and importance: It is difficult that doctors other than otorhinolaryngologist/radiologist find early postoperative maxillary cyst (POMC) because it tends to expand gradually with no symptoms over a period of years. Case presentation: A 60-year-old Japanese male who had previously undergone a bilateral Caldwell-Luc operation for the treatment of chronic sinusitis, experienced maxillary sinus floor elevation and implant placement. Eleven years after the implant placement, we discovered that the left POMC existed close to dental implants. Fortunately, dental implants still displayed proper osseointegration. Thus, the patient has been successfully treated for POMC, which had not been proper diagnosed before the implantation, by a marsupialization using nasal endoscopy and successfully preserved dental implant. Clinical discussion: Because the expanding POMC might result in dental implant failure after several years, we think that marsupialization is useful as a risk management for possible failure of dental implant close to POMC when it had not been found before maxillary sinus floor elevation and insertion of dental implant. Conclusion: Doctors should recognize that patients will have the risk of the dental implant failure after several years due to the expanding cyst when early POMC had not been diagnosed and treated properly before the implantation. Highlights: It is difficult that doctors other than otorhinolaryngologist/radiologist find early POMC before dental implantation. Marsupialization is useful as a risk management for possible failure of dental implant close to POMC. Patients will have the risk of the dental implant failure when early POMC had not been diagnosed before the implantation.